A Pragmatics Study of Implicature In Internet Memes And Jokes - Romadhon (The Doctoral Studies Program of Linguistics of Udayana University, 2024)
This paper examines the linguistic meaning of language in memes and jokes on the internet, focusing on the dynamic nature of online platforms like Reddit. It aims to understand the language distinctions underlying humor found in these platforms, which often defy accepted linguistic conventions. Implicit meaning, derived from the verb